2005
DOI: 10.1002/aoc.840
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectroscopic and X‐ray single‐crystal structure study of bis(2‐methoxy‐ethanolato)‐bis(8‐quinolinato)titanium(IV)

Abstract: OCH 3 ) 2 has been determined by single-crystal X-ray structure analysis. The geometry at titanium is a distorted octahedron, with the nitrogen atoms of quinolinate occupying the trans position with respect to oxygens of the 2-methoxyethoxy groups. The prepared quinolinate derivatives of titanium alkoxides are very stable towards hydrolysis and harsh conditions are required for hydrolytic cleavage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 18 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…A common method to couple phenol-containing partners is with LiHMDS as base; , however, in melt conditions, this gave negligible yields. On the basis of the literature, we propose that Lewis acids react with the phenol to form a neutral species of the type ArOAl­(OAlk) 2 or ArOTi­(OAlk) 3 , thus masking nucleophilic phenolate and making oxidation to N-aryl iminoquinones impossible. On the other hand, Lewis acids could also promote reductive elimination …”
Section: Resultsmentioning
confidence: 99%
“…A common method to couple phenol-containing partners is with LiHMDS as base; , however, in melt conditions, this gave negligible yields. On the basis of the literature, we propose that Lewis acids react with the phenol to form a neutral species of the type ArOAl­(OAlk) 2 or ArOTi­(OAlk) 3 , thus masking nucleophilic phenolate and making oxidation to N-aryl iminoquinones impossible. On the other hand, Lewis acids could also promote reductive elimination …”
Section: Resultsmentioning
confidence: 99%
“…Research suggests that the zinc analog of light-emitting materials AlQ 3 , zinc bis(8-hydroxyquinoline) [ZnQ 2 ] has a better injection efficiency, a lower operating voltage, and higher quantum yields than the commonly used AlQ 3 [6]. Thus zinc complexes may be potential candidates to enhance the efficiency and lifetime of OLEDs [7][8]. Meanwhile, Sapochak et al revealed that improvements of electroluminescence (EL) performance might be achieved by control of the oligomerization of 8-hydroxyquinoline chelates of Zn(II) and/or enhancement of the PL efficiency by judicious substitution of the ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the carbazole group has been commonly used as a functional building block in the fabrication of organic photoconductors, non-linear optical devices and OLEDs [12][13][14][15]. On the other hand, 8-hydroxyquinoline metal chelates are presently considered as one of the most reliable electro-transporting and emitting materials applied in molecularbased OLEDs for their thermal stability, high fluorescence, and excellent electron-transporting mobility [16][17][18]. In many cases, the electron-transporting mobility of zinc complexes with 8-hydroxyquinoline goes beyond that of aluminum complexes which is the most widely used electron-transporting material in OLEDs.…”
Section: Introductionmentioning
confidence: 99%